Integrated project delivery methods for energy renovation of social housing - Salcedo Rahola, Tadeo Baldiri (A+BE | Architecture and the Built Environment, 2015)
Optimised project delivery methods forsocial housing energy renovations European Social Housing Organisations (SHOs) are currently facing challenging times. The ageing of their housing stock and the economic crisis, which has affected both their finances and the finances of their tenants, are testing their capacity to stick to their aim of providing decent and affordable housing. Housing renovation projects offer the possibility of upgrading the health and comfort levels of their old housing stock to current standards and improve energy efficiency, and this solution also addresses the fuel poverty problems suffered by some tenants. Unfortunately, the limited financial capacity of SHOs is hampering the scale of housing renovation projects and the energy savings achieved. At the same time, the renovation of the existing housing stock is seen as one of the most promising alternative routes to achieving the ambitious CO2 emissions reduction targets set by European authorities – namely, to reduce EU CO2 emissions to 20% below their 1990 levels by 2020. The synergy between European targets and the aims of SHOs has been addressed by the energy policies of the member states, which focus on the potential energy savings achievable by renovating social housing. In fact, the European initiatives have prioritised energy savings in social housing renovations to such an extent that these are referred to as ‘energy renovations’. Energy renovation is therefore a renovation project with higher energy savings target than a regular renovation project. In total, European SHOs own 21.5 million dwellings representing around 9.4% of the total housing stock. Each SHO owns a large number of dwellings, which means there are fewer people to convince of the need to make energy savings through building renovations, maximising the potentially high impact of decisions. Moreover, SHOs are responsible for maintaining and upgrading their properties in order to continue renting them. As such, SHOs are used to dealing with renovations on a professional basis. The limited financial capacity of SHOs to realise energy renovations magnifies the importance of improving process performance in order to get the best possible outcomes. In the last 30 years numerous authors have addressed the need to improve the performance of traditional construction processes via alternative project delivery methods. However, very little is known about the specifics of renovations processes for social housing, the feasibility of applying innovative construction management methods and the consequences for the process, for the role of all the actors involved and for the results of the projects. The aim of this study is to provide an insight into the project delivery methods available for SHOs when they are undertaking energy renovation projects and to evaluate how these methods could facilitate the achievement of a higher process performance. The main research question is: How can Social Housing Organisations improve the performance of energy renovation processes using more integrated project delivery methods? The idea of a PhD thesis about social housing renovation processes originated from the participation of TU Delft as research partner in the Intelligent Energy Europe project SHELTER1 which was carried out between 2010 and 2013. The aim of the SHELTER project was to promote and facilitate the use of new models of cooperation, inspired by integrated design, for the energy renovation of social housing. The SHELTER project was a joint effort between six social housing organisations (Arte Genova, Italy; Black Country Housing Group, United Kingdom; Bulgarian Housing Association, Bulgaria; Dynacité, France; Logirep, France and Société Wallonne du Logement, Belgium), three European professional federations based in Brussels (Architects Council of Europe, Cecodhas Housing Europe and European Builders Confederation) and one research partner (Delft University of Technology). Research methods This thesis is composed of five studies. The first study is based on a literature review. The second study is based on five case studies from four countries (Belgium, Italy, France and United Kingdom), a questionnaire completed by 36 SHOs from eight countries and 14 interviews with experts from ten countries. The third is based on two French case studies and the fourth and fifth are based on 8 and 13 Dutch case studies respectively. Construction projects in housing involve a high number of professionals and take place over a long period of time. External factors, such as the economic and political situation or changes in construction or procurement regulations, can have a considerable influence on the construction process. Moreover, the specific characteristics of the construction sector of every country can also shape the process. In consequence, there are many interrelated variables that can have an influence on the dynamics of the process and on the outputs achieved. Research that seeks to understand the causes of changes in this process need to dig deeper into the internal and external characteristics of the process, which makes case study research the most appropriate research method for this type of study. The cases in each of the studies have been selected because innovative project management methods aiming for better collaboration between the participating actors were applied and because it was possible to gather high-quality data concerning these projects. The data were gathered mainly through interviews but other methods were also used: a questionnaire, observations and an analysis of tender documents. A protocol based on the recommendations of case study research literature was applied to assure the scientific validity of the data collected through the interviews. The case studies were complemented with a wide-ranging literature review covering scientific publications on project management in construction, mainly from the UK, the US, Australia, the Netherlands, Hong Kong and Finland. Reports from Intelligent Energy Europe projects were also reviewed, as well as legal texts relating to the tender options open to European social housing organisations. Construction management methods How to improve the performance of construction processes has long been and is still one of the key issues of the construction industry sector, social housing included. The performance of construction processes has been addressed from a range of perspectives in the construction management literature and diverse project management methods have been proposed. These methods are interrelated and in constant evolution. Moreover, different terminology is used to describe similar methods, which makes it difficult to obtain a clear picture. To simplify, three main perspectives or methods to improve the process integration and actors collaboration can be identified: the multi-project: supply chain integration; the single-project: integrated project delivery methods; and collaboration: partnering. Supply chain integration looks at the performance of the construction process from a multi-project perspective, relating the construction process to an industrial process. The project delivery method takes a single-project perspective into account because it is based on the premise that the complexity and singularity of any construction project will make it unique. Finally, partnering is focused on the characteristics of collaboration between the actors involved in the construction process. The singularity of renovation projects and the limitations of public procurement make the single project perspective the most feasible strategy for improving the process performance of social housing renovation projects. As such, the analysis of the project delivery methods is the most suitable method for improving the performance of renovation processes. The literature review shows that the more integrated project delivery methods are particularly indicated for construction projects with a high commitment to sustainability in general and for energy performance in particular. The literature review also reveals that the key factor in the process efficiency of all project delivery methods is collaboration between the actors involved in the project. Partnering methods can have a substantial positive influence on process performance. The study of the legal limitations imposed by the currently applicable public procurement Directive 2004/18/EC shows that even though a limited amount of tender options are available, is it possible to tender projects that apply integrated project delivery methods using the competitive dialogue procedure. Moreover, the recently approved but not yet enacted public procurement Directive 2014/24/ EU facilitates even further the use of competitive dialogue tenders for social housing energy renovations. Project delivery methods in European social housing energy renovations This study is based on five case studies, 36 questionnaires and 14 expert interviews, and identified four main project delivery methods for the energy renovation of social housing, namely: Step-by-Step (SBS) Design-Bid-Build (DBB) Design-Build (DB) Design-Build-Maintain (DBM). SBS can be considered a major renovation when the replacement of a series of building components eventually produces the same final result as a renovation project. In order to optimise the service lives of building components, an SHO might choose to split a major renovation project into a series of minor renovations. Cost-efficiency is achieved by procuring a large number of replacements only when a particular component has reached the end of its service life. This project delivery method will not usually include a design phase because these interventions usually involve replacing building products and systems. DBB, DB and DBM take place all at once and involve design companies, construction companies and maintenance companies. The difference between the three methods is the time frame for the involvement of the different actors and the contractual relationship with the SHO. In DBB, the various contracted parties are involved in the project one after the other, while in DB design companies and construction companies are involved during the same time period, and in DBM all three parties are involved during the same time period. Under DB, the SHO tenders the design and construction work in a single contract and under DBM it tenders the design, construction and maintenance work in a single contract. The contracted entity may be a single company, with or without subcontractors, or a consortium. SBS and DBB are the most commonly used project delivery methods for social housing renovation projects, although DB and DBM are also used for a small number of projects. The vast majority of SHOs use more than one project delivery method simultaneously, mainly a combination of SBS and DBB. For new-build projects, DBB has traditionally been considered the most commonly used project delivery method; however, our survey revealed that it is in fact the second most commonly used project delivery method after SBS. The DBM approach has the maximum potential for delivering energy savings, because it facilitates collaboration between the different actors and promotes their commitment to achieving project goals. Furthermore, DBM offers greater price certainty and less risk of design failure compared to other project delivery methods. However, the project delivery method cannot guarantee the achievement of targeted energy savings by itself. Numerous factors need to be taken into account when considering a change in the project delivery method. The property asset management of the dwelling stock that is renovated using SBS, which focuses on building elements and systems, is completely different from the property asset management of the dwelling stock renovated by DBB, DB or DBM, which focuses on entire properties. It is therefore unlikely that SHOs that are already applying SBS will switch to another project delivery method. Switching between DBB to DBM, or to DB, is feasible since they are similar in terms of property asset management. A change of project delivery method could be motivated by the use of energy performance guarantees offered by energy performance contracting, which is possible in cases where DBM is used. However, this choice is not suitable for all SHOs. For example, if an SHO has an in-house design team and changes to DBM (or DB), its design team will not be involved in the project as the contractor will have its own design staff. If an SHO has a corporate responsibility towards SMEs and changes to DBM (or DB), it will be more difficult to keep SMEs directly involved since they will need to organise themselves into consortia. And finally, if an SHO already has a contract with a maintenance company to manage their entire housing stock, changing to DBM will create a conflict in their maintenance management, since for every property where DBM has been used, a different maintenance company will take charge of maintenance. Energy efficiency in French social housing renovations via Design-Build-Maintain The study is based on the analysis of two social housing renovation projects, implemented by two French SHOs: the renovation of 14 dwellings in a three-storey apartment block in Nurieux-Volognat (in south-eastern France) by the Dynacité SHO; and the renovation of 231 dwellings in four apartment blocks (ranging from 6 to 10 storeys) in Vitry-sur-Seine (in the southern suburbs of Paris) by the Logirep SHO. The data on the case studies were obtained from: the tender documents (call for offers, specifications and preliminary designs); observation during the negotiation phase in the case of Dynacité; interviews, carried out after the construction work was finished, with the social housing renovations manager, the social housing project manager, the construction company, the architect’s office and the maintenance company involved in both cases; and the evaluation reports produced by project managers at the SHOs. The results demonstrate that it is possible to engage design companies, construction companies and maintenance companies to achieve energy savings that exceed those stipulated by the SHO and to obtain a guarantee of results. This approach also makes it possible to shorten the duration of a project, while limiting the costs involved to approximately the equivalent of those incurred in DBB renovation projects. The collaborative set-up of the DBM process also results in improved relations between the actors involved. However, an analysis of these relationships indicated that there is still room for improvement, particularly with regard to the maintenance company. In order to guarantee the benefits of implementing a DBM process, it is necessary for the SHO to put in place the following: realistic but ambitious minimum requirements; clear and measurable award criteria that stress the importance of achieving high energy savings; and a guarantee mechanism that is fair and robust. Moreover, the SHO needs to ensure that the scale of the contract is large enough to guarantee that any compensation paid to non-selected candidates does not adversely affect the total cost of the project and that the SHO’s maintenance strategy must be flexible enough to handle maintenance contracts that are project-related as well as maintenance stock-related contracts. Competitive tenders for integrated contracts for social housing renovation projects The study, which is based on an analysis of eight renovation projects undertaken by SHOs in the Netherlands, shows that Dutch SHOs apply a range of mechanisms in order to influence the ambition, collaboration and long-term view of the consortia that participate in competitive tenders for integrated renovation projects. Their aim is to improve the quality of the construction process and thereby enhance the quality of the output. The scale of the ambition is raised, in first place, through the competitive character of the selection procedure. Several candidates are invited to the tender but only the best will be selected. Secondly, the minimum performance level is defined above common standards by setting high but achievable minimum requirements. Thirdly, the candidates are encouraged to perform at their best by being rated by award criteria that evaluate their performance. The findings show that SHOs are not all singing from the same song sheet when it comes to determining the level of ambition they require from their candidates in relation to the key issue of energy saving. Collaboration is encouraged mainly by setting a very tight deadline for the design proposals, a period of just 11 weeks on average. The consortium members are thus required to work closely together in order to get the proposals out on time and make a convincing pitch in a presentation. The findings show that the procedures with higher numbers of meetings between the SHO and the consortium during the design proposal period appeared to increase collaboration with the SHO. Other mechanisms, such as setting conditions for the nature of the candidates or proposing team coaches, were implemented to a lesser extent and not regarded as appropriate by all SHOs. A longer-term view is promoted by including an optional long-term maintenance contract for the renovated dwellings. The results of this strategy were not as good as expected, however, because the majority of the candidates did not integrate maintenance into their proposal, preferring to make an additional and separate maintenance offer. The SHOs did not include maintenance as an integral part of the renovation project because they were afraid of the possible implications of a long-term maintenance contract on a project basis for their general building stock maintenance strategy and their in-house maintenance teams. The role of the architect using integrated contracts for social housing renovation projects The focus of previous studies is on analysing the implementation of integrated project delivery methods from the demand side, the social housing organisation. However, it has been also identified that the use of integrated project delivery methods have consequences for the supply side actors. Especially for the architect because his central role in the design process could be affected. This study, which is based on the analysis of the role of the architect in thirteen renovation projects that used integrated contracts, concludes that the main role of the architect, as having principal responsibility for the design choices made, does not change when integrated contracts are used. However, the decision-making power of the architect does decrease. With the use of integrated contracts, the main contractor and some specialised contractors can also influence the design choices – an influence that they would not otherwise have. In cases where the main contractor plays an active leading role in the consortium, the reduction of the decision-making power of the architect may become even more evident, and in the opinion of some architects, turn the role of architect into a role more akin to that of technical and aesthetic advisor. The changes in how design decisions are taken do not have a negative impact on the quality of the relationship between the architect and the SHO, and has a positive influence on the quality of the relationship between the architect and the construction companies involved in the project. Some changes were reported relating to the workload for each project compared to Design-Bid-Build projects. In some cases, architects were no longer involved in project management tasks, while in other cases architects were assigned additional responsibilities, such as communicating with tenants. It is not possible, therefore, to establish a direct relationship between the use of integrated contracts and the size of the architect’s workload. Where there is an evident change is in the distribution of the workload and payment for the work done for the integrated contracts that have been tendered through a competitive procedure (seven of the thirteen projects analysed). In projects tendered using a competitive procedure, the work of the architect is condensed into a shorter timeframe (42% shorter than with a non-competitive procedure) and there is a higher risk that the working hours will not be paid in full if the consortium is not awarded the contract. Conclusions In order to improve the performance of energy renovation processes undertaken by social housing organisations, the Design-Build-Maintain project delivery method offers the best opportunity to facilitate the active involvement of all actors, obtain the best possible project performance and to guarantee the quality of the end results. However, given the characteristics of each SHO and the characteristics of the renovation projects, DBM is not always the project delivery method chosen. If DBM is not used, other simpler management mechanisms, such as the early involvement of contractors or the use of in-house maintenance companies as advisors, should be considered to contribute to better process performance. In order to apply the DBM project delivery method successfully, it is necessary for the SHO to focus its efforts on designing a tender procedure that maximises the potential of the entire project delivery method. Choosing a competitive tender procedure that allows the dialogue with candidates. Defining performance-based specifications with realistic but ambitious minimum requirements and a set of clear and measurable award criteria that stress the importance of achieving energy savings. Defining a performance guarantee mechanism that is fair and robust. Setting up tender process conditions that facilitate communication between the candidates and the SHO and that promote team working among the candidate team (consortium). The members of the candidate team, the consortium, also need to adapt to the new game rules. Specifically the architect needs to gain more managerial skills in order to keep his leading design decision position and become more of a team integrator. Future research should consider the changes in the roles of the other consortium members and the best consortium structures to ensure a good product quality and the fair treatment of all the parties involved.